Payment Efficiency and Tax Compliance Issues in User Experiences with Zakat Institution’s Online Services - Wardana, Arief Budi (International Journal of Zakat, 2023)
The Indonesian government has issued regulation of zakat as a tax deduction for taxable income to increase the nationwide zakat collection. This study is a personal reflection, explaining the author’s experience in using online zakat services provided by the National Zakat Agency Republic of Indonesia (BAZNAS). The exploratory storyline employs the E-S-QUAL & E-RecS-QUAL framework, adding the dimension of compliance to the tax regulation. The findings practically imply that BAZNAS’ online services well perform in all measured dimensions for zakat payment purposes. However, efforts are required to spend more time when the author tests the feature of zakat payment slips that comply with the local tax regulations. Hence, zakat institutions, e.g., BAZNAS, are advised to inform zakat as a factor in deducting income tax from their online services.